Power, Obedience, and Moral Struggle: A Psychoanalytic Analysis of Leadership in Qs. Al-Baqarah [2]: 246–251 - Ali Nurdin; Ahmad, Amiril; Ainul Mardiah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
This article examines the psychological dynamics of leadership within the context of the Israelites, focusing on the analysis of Qs. Al-Baqarah: 246-251 through the psycho-literature approach. The study aims to understand the personality conflicts of key figures in the narrative based on Sigmund Freud’s personality structure: id, ego, and superego. The research employs a qualitative method using library research and content analysis. The findings reveal that the story of the Israelites contains significant moral lessons, particularly in the context of leadership and responses to challenges. The conflict between instinctual drives (id), rationality (ego), and moral values (superego) is clearly reflected in the decisions and actions of the characters, representing the psychological state of the society at that time. Adherence to moral and spiritual values, represented by the superego, is shown to be a critical factor in achieving success and blessings. This study emphasizes the importance of balancing personality components in building effective leadership and highlights the relevance of Qur'anic narratives as an enduring source of moral guidance.